2015
DOI: 10.1002/2015jd023522
|View full text |Cite
|
Sign up to set email alerts
|

Complex refractive index of secondary organic aerosol generated from isoprene/NOx photooxidation in the presence and absence of SO2

Abstract: We report the first measurements of the complex refractive index (RI) at 375, 405, 532, and 781 nm for secondary organic aerosol (SOA) generated from isoprene/NO x photooxidation. At all wavelengths studied, slightly greater real components of the RI were observed for the SOA generated in the absence of SO 2 compared with those generated in its presence. Considering the chemical properties, the differences in the oxidation state and/or ratio of particle density to molecular weight of compounds in the SOA are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 63 publications
8
42
0
Order By: Relevance
“…All values of RI(n) at 375 nm were larger than those at 532 nm with difference of 0.022-0.062. The real and imaginary parts of RI increased as the wavelength decreased, which was in good accordance with previous studies (Moise et al, 2015;Flores et al, 2014a, b;Lin et al, 2015;Liu et al, 2015;Nakayama et al, 2013Nakayama et al, , 2018Nakayama et al, , 2015. For example, Liu et al (2015) found the values of RI(n) of toluene-derived secondary organic material decreased by approximately 0.1 when wavelength changed from 240 to 800 nm (Liu et al, 2015).…”
Section: General Results Of the Experimentssupporting
confidence: 91%
See 1 more Smart Citation
“…All values of RI(n) at 375 nm were larger than those at 532 nm with difference of 0.022-0.062. The real and imaginary parts of RI increased as the wavelength decreased, which was in good accordance with previous studies (Moise et al, 2015;Flores et al, 2014a, b;Lin et al, 2015;Liu et al, 2015;Nakayama et al, 2013Nakayama et al, , 2018Nakayama et al, , 2015. For example, Liu et al (2015) found the values of RI(n) of toluene-derived secondary organic material decreased by approximately 0.1 when wavelength changed from 240 to 800 nm (Liu et al, 2015).…”
Section: General Results Of the Experimentssupporting
confidence: 91%
“…Jaoui et al (2008) showed that the addition of SO 2 would make the color of the SOA generated via the photooxidation of α-pinene and toluene darker and browner, and oligomers and nitrogenous organic compounds were detected in the SOA extracts (Jaoui et al, 2008). Nakayama et al (2018) investigated the effect of SO 2 on the optical properties of isoprene under various NO x concentrations and oxidation pathways (Nakayama et al, 2015(Nakayama et al, , 2018. However, more research is needed on the role of SO 2 in the subsequent optical properties of SOA formed from various VOCs.…”
Section: Introductionmentioning
confidence: 99%
“…For PAX, the extinction coefficiency data (Q ext ), scattering coefficiency (Q scat ), and absorption coefficiency (Q abs ) could be obtained directly. The calculation methods were similar to those used in the previous studies using the PAX at 375 nm (Nakayama, Sato, et al, 2015;Nakayama, Suzuki, et al, 2015).…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
“…BrC can also be emitted directly from coal burning (Yan et al, 2017) and biogenic release of fungi, plant debris and humic matter (Rizzo et al, 2011(Rizzo et al, , 2013. In addition, recent studies suggested that secondary BrC can be formed through various reaction pathways, including photooxidation of aromatic volatile organic compounds (VOCs) (Lin et al, 2015;Liu et al, 2016), reactive uptake of isoprene epoxydiols onto preexisting sulfate aerosols (Lin et al, 2014), aqueous oxidation of phenolic compounds and α-dicarbonyls (Chang and Thompson, 2010;Nozière and Esteve, 2005;Smith et al, 2016;Yu et al, 2014;Xu et al, 2018), and reactions of ammonia or amines with carbonyl compounds in particles or cloud droplets (Nozière et al, 2007;Laskin et al, 2010;Updyke et al, 2012;Nguyen et al, 2012;De Haan et al, 2018;Powelson et al, 2014). However, atmospheric oxidation processes may also cause "photobleach" -photodegradation of BrC into lesslight-absorbing compounds (Lee et al, 2014;Romonosky et al, 2015;Sumlin et al, 2017), which may complicate the understanding of BrC in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%